K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

23 tháng 6 2020

Bài làm:

Ta có: \(A=x^2+xy-x+2020=x\left(x+y\right)-x+2020=x-x+2020=2020\)

Vậy A=2020

Học tốt!!!!

23 tháng 6 2020

Ta có:\(A=x^2+xy-x+2020\)

\(\Leftrightarrow A=x.\left(x+y\right)-x+2020\)

\(\Leftrightarrow A=x.1-x+2020\)

\(\Leftrightarrow A=2020\)

Vậy \(A=2020\)

15 tháng 10 2023

\(a,A=x^2+y^2\\=x^2-2xy+y^2+2xy\\=(x-y)^2+2xy\\=2^2+2\cdot1\\=4+2\\=6\)

\(b,x+y=1\\\Leftrightarrow (x+y)^3=1^3\\\Leftrightarrow x^3+3x^2y+3xy^2+y^3=1\\\Leftrightarrow x^3+3xy(x+y)+y^3=1\\\Leftrightarrow x^3+3xy\cdot1+y^3=1\\\Rightarrow A=1\)

15 tháng 10 2023

a) Ta có:

\(x-y=2\)

\(\Rightarrow\left(x-y\right)^2=2^2\)

\(\Rightarrow x^2-2xy+y^2=4\)

Mà: \(xy=1\)

\(\Rightarrow\left(x^2+y^2\right)-2\cdot1=4\)

\(\Rightarrow x^2+y^2=4+2\)

\(\Rightarrow x^2+y^2=6\)

b) Ta có: 

\(x+y=1\)

\(\Rightarrow\left(x+y\right)^3=1^3\)

\(\Rightarrow x^3+3x^2y+3xy+y^3=1\)

\(\Rightarrow x^3+3xy\left(x+y\right)+y^3=1\) 

Mà: x + y = 1

\(\Rightarrow x^3+3xy\cdot1+y^3=1\)

\(\Rightarrow x^3+3xy+y^3=1\)

20 tháng 7 2023

Bài 6:

M= 2.2 - 2.3+3.2.3

M= 4 - 6 + 18

M= 20

Bài 7: 

P= 1.2 - 5.-1.-2 + 8.-2.2

P = 2 -10 -32

P= -44

Bài 8:

A (thiếu dữ kiện bn ơi)

B= -1.2 . 3.2 + -1.3 +3.3 +-1.3

B= -2 . 6 + -3 + 9 +-3

B= -2 . 6 - 3 + 9 - 3

B= -12 - 3 + 9 - 3

B= -9

a: \(A=x^2+y^2=\left(x+y\right)^2-2xy=15^2-2\cdot50=115\)

c: \(x-y=\sqrt{\left(x+y\right)^2-4xy}=\sqrt{15^2-4\cdot50}=5\)

\(C=x^2-y^2=\left(x+y\right)\left(x-y\right)=15\cdot5=75\)

2 tháng 12 2023

Ta có \(x^2+y^2+xy+x=y-1\)

\(\Leftrightarrow2x^2+2y^2+2xy+2x-2y+2=0\)

\(\Leftrightarrow\left(x+y\right)^2+\left(x+1\right)^2+\left(y-1\right)^2=0\)

\(\Leftrightarrow\left\{{}\begin{matrix}x+y=0\\x+1=0\\y-1=0\end{matrix}\right.\)

\(\Leftrightarrow\left\{{}\begin{matrix}x=-1\\y=1\end{matrix}\right.\)

\(\Rightarrow B=\left(-1+1-1\right)^{2023}\) \(=\left(-1\right)^{2023}\) \(=-1\)

2 tháng 12 2023

bvbbbvvbvv

7 tháng 6 2020

A=x(x+y-1)+2019

=>A=x.9+2019=2019

(do x+y=1)

28 tháng 12 2021

B

\(A=\left(x-y\right)\left(x^2-xy\right)-x\left(x^2+2y^2\right)\)

\(=x^3-x^2y-x^2y+xy^2-x^3-2xy^2\)

\(=-2x^2y-xy^2\)

\(=-2\cdot2^2\cdot\left(-3\right)-2\cdot\left(-3\right)^2\)

\(=8\cdot3-2\cdot9\)

=6